Elucidation of the Mechanisms of Long-Distance mRNA Movement in a Nicotiana benthamiana/Tomato Heterograft System. Issue 2 (2nd May 2018) - Xia, Chao; Zheng, Yi; Huang, Jing; Zhou, Xiangjun; Li, Rui; Zha, Manrong; Wang, Shujuan; Huang, Zhiqiang; Lan, Hai; Turgeon, Robert; Fei, Zhangjun; Zhang, Cankui
Abstract : Messenger RNA is degraded as it moves through the tomato phloem, and the mobility of a transcript cannot be reliably predicted based on its abundance in the Nicotiana benthamiana leaf or on whether it harbors a tRNA-like structural motif.​ Abstract: Recent heterograft analyses showed that large-scale messenger RNA (mRNA) movement takes place in the phloem, but the number of mobile transcripts reported varies widely. However, our knowledge of the mechanisms underlying large-scale mRNA movement remains limited. In this study, using a Nicotiana benthamiana /tomato ( Solanum lycopersicum ) heterograft system and a transgenic approach involving potato ( Solanum tuberosum ), we found that: (1) the overall mRNA abundance in the leaf is not a good indicator of transcript mobility to the root; (2) increasing the expression levels of nonmobile mRNAs in the companion cells does not promote their mobility; (3) mobile mRNAs undergo degradation during their movement; and (4) some mRNAs arriving in roots move back to shoots. These results indicate that mRNA movement has both regulated and unregulated components. The cellular origins of mobile mRNAs may differ between herbaceous and woody species. Taken together, these findings suggest that the long-distance movement of mRNAs is a complex process and that elucidating the physiological roles associated with this movement is challenging but remains an important task for future research.